Enhancing Students’ Speaking Proficiency through Project-Based Learning and AI-Supported Tools (Orai App) - Elviani, Mutia; Sihombing, Tahan H.J.; Hamdanur,, Roobby; Liani, Ghustiva; Nuraini, Nuraini (International Journal of Education, Language, and Religion, 2025)
This study examines the effectiveness of integrating Project-Based Learning (PBL) with AI-supported tools, specifically the Orai application, to enhance students’ English-speaking proficiency. Conducted as a Classroom Action Research (CAR), the study involved two cycles, each including pre-tests and post-tests, assessed using the Speaking Rubric proposed by O'Malley and Pierce (1990). The participants were 25 first-semester students from the MICE (Meetings, Incentives, Conventions, and Exhibitions) study program enrolled in the English 1 course at the Business Administration Department of Politeknik Negeri Medan during the 2025/2026 academic year. This study used a mixed-methods approach, combining quantitative and qualitative data to provide a comprehensive analysis of the intervention. The quantitative data revealed significant improvements in students' speaking proficiency. The pre-test mean score was 75.28, and by the post-test, the average score had increased to 86.00, reflecting a 10.72-point improvement. Additionally, Cycle 1 indicates an average increase of 5.96 points (from 75.28 to 81.24), while Cycle 2 shows a further 2.6-point improvement (from 81.24 to 83.84). This demonstrates a consistent upward trend in students' speaking skills throughout the intervention. Meanwhile, qualitative data further supports these findings, highlighting increased confidence, engagement, and active participation among students, particularly in real-world tasks related to tourism and hospitality. However, the intervention also revealed areas for further refinement. There is a need for more personalized support from instructors to address individual learning challenges, and a wider range of topics to cater to students' diverse interests and career aspirations. The integration of AI tools supported students in practicing individually and fostered greater confidence and more active engagement in collaborative projects. The results suggest that applying PBL with AI-assisted applications is an effective instructional strategy to address speaking challenges in English language learning at the tertiary level.